2014
DOI: 10.1002/biot.201400499
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic switchgrass (Panicum virgatum L.) biomass is increased by overexpression of switchgrass sucrose synthase (PvSUS1)

Abstract: Sucrose synthase (SUS) converts sucrose and uridine di-phosphate (UDP) into UDP-glucose and fructose. UDP-glucose is used by the cellulose synthase to produce cellulose for cell wall biosynthesis. For lignocellulosic feedstocks such as switchgrass, the manipulation of cell walls to decrease lignin content is needed to reduce recalcitrance of conversion of biomass into biofuels. Of perhaps equal importance for bioenergy feedstocks is increasing biomass. Four SUS genes were identified in switchgrass. Each gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 50 publications
(69 reference statements)
2
30
0
Order By: Relevance
“…Poovaiah et al . (Poovaiah et al ., ) overexpressed a SuSy transgene in the biofuel feedstock switchgrass ( Panicum virgatum ), achieving increased height and biomass in some transformants. In Populus alba x grandidentata (hybrid poplar), overexpression of SuSy caused increases in soluble carbohydrates and cellulose, and a decrease in cell wall‐derived arabinose (Coleman et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Poovaiah et al . (Poovaiah et al ., ) overexpressed a SuSy transgene in the biofuel feedstock switchgrass ( Panicum virgatum ), achieving increased height and biomass in some transformants. In Populus alba x grandidentata (hybrid poplar), overexpression of SuSy caused increases in soluble carbohydrates and cellulose, and a decrease in cell wall‐derived arabinose (Coleman et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to the reduction in photosynthate partitioning towards generative development, relative to wild-type plants, under floral induction conditions. Enhanced biomass production as a result of the flowerless trait could be useful in various energy crops (Kalluri et al, 2014;Poovaiah et al, 2015;Torney et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Taking together, the function of SuS is for the sucrose synthesis only in August, however for sucrose decomposition for other months. Poovaiah et al (2015) increased the biomass of switchgrass through overexpression of switchgrass sucrose synthase gene PvSUS1. This suggested that cassava starch might be increased through similar approach.…”
Section: The Time Course Of Cassava Leaf Sus Synthesis Direction and mentioning
confidence: 99%